Vibration suppression of bridges under moving loads using the structure-immittance approach. (1st December 2021) - Zhang, Sara Ying; Sheng, Xi; Jiang, Jason Zheng; Zhou, Haijun; Ren, Wei-Xin; Zhang, Zi-Hang
Highlights: Absorber design methodology incorporating inerters for a bridge-train system is proposed. The structure-immittance approach is applied to obtain the optimum inerter-based configuration with pre-determined complexity. The proposed absorber is robust against both the bridge parameter changes and component value variance. The proposed absorber outperforms an optimised TMD in bridge vibration mitigation under three types of railway excitations. Graphical abstract: Abstract: This paper presents the possibility of suppressing the train-induced vibration on bridges using a linear passive vibration suppression device incorporating inerter. The inerter is a two-terminal mechanical element with the property that the applied force is proportional to the relative acceleration across its terminals. The inerter has been applied to various engineering structures where performance benefits have been identified. However, currently these studies are either limited to simple network configurations with moderate performance improvement, or resulted in complicated configurations with a large number of elements which are impractical for real-life applications. In addition, the potential of using inerter-based absorbers for suppressing the train-induced bridge vibrations has not been taken into consideration. In this paper, a simplified bridge model equipped with a vibration suppression device subjected to series of moving forces is presented. The structure-immittance approach, which can cover all networks with pre-determined numbers of each element type, is adopted for the identification of the optimal absorber configurations. Numerical studies for two bridges, the THSR and the Kum-gang, under three types of railway excitations, the French T.G.V., the German I.C.E. and the Japanese S.K.S. are conducted. It is demonstrated that the overall performance of the bridge can be improved by using the proposed inerter-based configuration. It is also checked that the absorber stroke is much smaller than the inner space of bridge box girder, indicating the practical installation of the absorber. Furthermore, the robustness of the proposed absorber is verified by sensitivity analysis subjected to the change of bridge parameters and the device component values.